Comparison of Cognitive Functions between Paroxysmal and Persistent Atrial Fibrillation Patients without Clinical Stroke - Caepy Gomer; Paulus Anam Ong; Sobaryati Sobaryati; Badai Bhatara Tiksnadi (International Journal of Integrated Health Sciences, 2020)
Objective: To compare cognitive functions between paroxysmal and persistent atrial fibrillation patients without clinical stroke, in terms of MoCA-Ina total score and MoCA-Ina cognitive subdomains scores. Methods: A comparative study that compared MoCA-Ina scores between paroxysmal and persistent AF patients without clinical stroke, who came for treatment at the Cardiology Clinic Dr. Hasan Sadikin General Hospital, Bandung and Dustira Hospital, Cimahi from September 2018–January 2019. Results: Sixty four subjects were recruited, consisted of 24 paroxysmal and 40 persistent AF patients. There were no difference in clinical characteristics between two groups, except that there were more subjects in the persistent AF group using anticoagulants therapy: 97.5% vs 62.5% (p=0.005) and more prevalence of type 2 Diabetes Mellitus in the paroxysmal AF group: 25% vs 2.5% (p=0.009). Cognitive impairment (MoCA-Ina score <25) were seen in 70.8% of paroxysmal AF group and 82.5% of persistent AF group (p=0.274). The mean MoCA-Ina total score in the paroxysmal and persistent AF groups were 21.04±4.75 vs 20.70±4.21 (p=0.989), respectively. The median MoCA-Ina cognitive subdomains scores were similar for the two groups (p>0.05).Conclusion: There were no differences in cognitive functions between paroxysmal and persistent AF patients, both in terms of MoCA-Ina total score and MoCA-Ina cognitive subdomains scores, although in both groups had cognitive decline.